Effect of Disturbance in Tree Diversity, Carbon Stock and Regeneration in the Community Forests of Dang, Nepal - Chaudhary, Sujan; Dangi, Chiranjibi; Karki, Nabin Singh; Adhikari, Saroj; Kandel, Samundra; Devkota, Mohan Prasad (Banko Janakari, 2026)
The tropical forests of Nepal face significant threats due to disturbances like grazing, human activities, forest fires, deforestation, and construction. This study aimed to assess the impact of disturbances on tree diversity, carbon stock, and regeneration and regeneration in two community forests in Dang, Western Nepal: Pathivara Community Forest (highly disturbed) and Janakalyan Community Forest (less disturbed). In the present study, data from 60 circular sample plots (30 in each forest) were analyzed. Soil samples, collected to a depth of 30 cm, were tested for organic matter, nitrogen, potassium, phosphorus, and pH content. Eighteen tree species across 15 genera and 10 families were recorded, where a higher diversity was observed in the less disturbed forest (LDF) compared to the highly disturbed forest (HDF). Shorea robusta was the dominant species in both forests, contributing significantly tocarbon storage. The mean carbon stock in HDF and LDF was 46.48 Mg/ha and 72.72 Mg/ha, respectively. The overall regeneration was poor in both forests, particularly among saplings compared to standard community forest inventory guidelines. LDF showed higher organic matter, nitrogen, and potassium content, while HDF had greater phosphorus levels. The study highlighted the adverse effects of disturbances on forest quality and regeneration. The less disturbed forest (LDF) exhibits better carbon storage, soil fertility, and species diversity compared to the highly disturbed forest (HDF). To improve forest conditions, it is recommended to enhance conservation efforts, reduce anthropogenic pressures, and implement effective management practices to support natural regeneration, particularly for saplings.